2004
DOI: 10.1111/j.1365-3156.2004.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of artemether‐lumefantrine and artesunate‐mefloquine for treatment of uncomplicated Plasmodium falciparum malaria in Luang Namtha Province, Lao People's Democratic Republic

Abstract: SummaryThe efficacy of the six-dose regimen of artemether-lumefantrine was compared with the combination of artesunate and mefloquine in a randomised, comparative trial in Luang Namtha Province, Northern Laos. Of 1033 screened patients, 201 were positive for Plasmodium falciparum; 108 patients of all age groups (2-66 years) with acute, uncomplicated P. falciparum malaria were enrolled in the study, 100 of whom were followed-up for 42 days. Fifty-three patients received artemether-lumefantrine and 55 received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 18 publications
8
19
0
1
Order By: Relevance
“…These predicted day 7 capillary plasma concentrations were approximately equivalent to the median venous plasma concentrations of 310 ng/ml (range, 94 to 1,364 ng/ml) determined by using the previously characterized relationship between capillary and venous concentrations (49). This is considerably lower than the corresponding values previously reported in nonpregnant adults and pediatric patients with multiresistant malaria in Thailand, Cambodia, and the Lao People's Democratic Republic (10,29,42,47). Price et al (42) reported a median day 7 venous plasma lumefantrine concentration of 528 ng/ml (range, 49 to 5,175 ng/ml) in Karen patients (n ϭ 201) receiving the same standard treatment of artemether-lumefantrine.…”
Section: Discussionsupporting
confidence: 48%
“…These predicted day 7 capillary plasma concentrations were approximately equivalent to the median venous plasma concentrations of 310 ng/ml (range, 94 to 1,364 ng/ml) determined by using the previously characterized relationship between capillary and venous concentrations (49). This is considerably lower than the corresponding values previously reported in nonpregnant adults and pediatric patients with multiresistant malaria in Thailand, Cambodia, and the Lao People's Democratic Republic (10,29,42,47). Price et al (42) reported a median day 7 venous plasma lumefantrine concentration of 528 ng/ml (range, 49 to 5,175 ng/ml) in Karen patients (n ϭ 201) receiving the same standard treatment of artemether-lumefantrine.…”
Section: Discussionsupporting
confidence: 48%
“…The results show the excellent efficacy and tolerability of both AL and AS-MQ in Northern Laos (Stohrer et al, 2004). In bordering Thailand, similar cure rates were reported for the AS-MQ combination after 42 days (89 and 98%) (Price et al, 1997;Suputtamongkol et al, 2003), as well as for 28 days follow-up (cure-rates 98-100%) (van Vugt et al, 1998).…”
Section: -Day In Vivo Protocol To Test Acts Efficacysupporting
confidence: 63%
“…However, the concentration in pregnant women was 2-fold higher than what had been observed in pregnant Thai patients (19). It is also higher than the concentrations previously reported in nonpregnant adults and pediatric patients in Tanzania Ifakara), Thailand, Cambodia, and the Lao People's Democratic Republic (22,24,45,46). Higher day 7 LF levels in the present study may be due to the administration of a standard recommended adult dose of AL with food (5) to all patients regardless of the patient's body weight.…”
Section: Discussionmentioning
confidence: 58%